LIFE QUALITY OF PATIENTS ACCORDING TO GENDER AND THE FORM OF NON-ST-ELEVATION ACUTE CORONARY SYNDROME - M. A. Ayrapetian; E. E. Luchinkina; I. G. Gordeev; E. O. Taratukhin (Российский кардиологический журнал, 2017)
Aim. To assess the specifics of psychoemotional state of adult patients with non ST elevation acute coronary syndrome (NSTEACS) in 6 months post hospitalization.Material and methods. Totally, 101 patient included, with non-obstructive lesion of coronary flow. Groups were formed by gender: group 1 — 51 females, group 2 — 50 males. Mean age: women 50,5±4,7 y. o., men 46,7±6,8 y. o. Patients were also selected to subgroups by NSTEACS type: subgroup A — unstable angina (UA), subgroup B — myocardial infarction. Patients were questionned by phone in 6 months after discharge. The questionnaire included key points about health, emotional balance, physical activity and life quality.Results. There are gender differences in life quality constituents between men and women. In questions on general health state 6% of women replied that are not satisfied with their health, in men — 2%; satisfactorily graded their health state 27% of women and 38% of men, good — 47% and 46%, excellent — 20% and 14%, respectively. Pre-morbid physical activity at work was saved in 45% of men and 32% of women; active life style retained 47% of women and 42% of men. Men more often felt hopelessness (43% and 12%; p<0,01), as women mostly pointed on irritability and sleeplessness (35% and 28%; p>0,05) and were unsatisfied with their psychological state (31% and 6%; p<0,05). In both groups patients experienced the feeling of lost worth of living, women — more often (7% and 4%; p>0,05), however men noted loss of interest to former habits (13% и 22%; р>0,05). The specifics in subtypes of NSTEACS was also noted.Conclusion. Regardless an individuality of the meanings of life quality, experiences, coping, there is gender specifics, as specifics in NSTEACS subtype. The specifics can be included as a part of patient-centered work with post-ACS patients.